How to Protect Integrity of Research in the Age of Social Media? - Franzen-Waschke, Ute; Isaacson, Sam (GILE Journal of Skills Development, 2026)
Artificial Intelligence (AI), data-driven decisions and evidence-based approaches appear to become increasingly important when establishing credibility and authority in non-academic circles. Knowing the difference between an experiment meant to illustrate a point, doing research for a degree where rigor and ethics are crucial, and doing research in a business context have transformed into a skill not only relevant for academics, but progressively for anyone reading articles on the Internet and on social media. On social media algorithms drive visibility not rigor and ethics. An experiment conducted on LinkedIn in October 2025 describes what happens when two nearly identical articles are posted at the same time and how algorithms drive visibility and conversations. Simultaneously, a critical reflection of how to identify “good research” from a practitioners’ perspective is provided. Finally, assessment criteria for the layperson are provided to foster awareness and to promote skill development and literacy in an era in which making sense to data in a self-reliant manner are indispensable across all social stratums. Key findings of the experiment highlight the importance of scientific rigor also in online research and demonstrate how easily bias and uncontrolled variables, such as resharing behaviour, can distort outcomes and conclusions. Subsequent studies may refine this initial experiment by employing more rigorous methodologies and adhering to established ethical standards in research.